2022
DOI: 10.3390/ijerph192315935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Length of Hospital Stay for Community-Acquired Infections Due to Enteric Pathogens, Influenza Viruses and Multidrug-Resistant Bacteria: A Cross-Sectional Study in Hungary

Abstract: Community-acquired infections (CAI) can affect the duration of care and mortality of patients. Therefore, we aimed to investigate these as well as factors influencing the length of hospital stay in patients with CAI due to enteric pathogens, influenza viruses and multidrug-resistant (MDR) bacteria. We obtained data on 531 patients with CAI from the medical databases of a Hungarian university hospital and analyzed their characteristics using a regression model. Patients with MDR bacterial infection had the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…However, with the misuse and/or overuse of these types of drugs, there is the risk of antibiotic resistance (AMR), which is one of the top-ten global public health threats, according to the World Health Organization [ 24 ]. A 2022 cross-sectional study in Hungary revealed that multidrug-resistant (MDR) bacterial infections caused extended hospital stays and increased patient mortality [ 25 ]. One option to solve this problem could be to apply silver ions, which are frequently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the misuse and/or overuse of these types of drugs, there is the risk of antibiotic resistance (AMR), which is one of the top-ten global public health threats, according to the World Health Organization [ 24 ]. A 2022 cross-sectional study in Hungary revealed that multidrug-resistant (MDR) bacterial infections caused extended hospital stays and increased patient mortality [ 25 ]. One option to solve this problem could be to apply silver ions, which are frequently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, it is extensively researched for biomedical applications [ 21 , 33 43 ]. It is also known that PSI turns into polyaspartic acid (PASP) at physiological conditions, which is a degradable biomaterial [ 24 – 25 36 37 ].…”
Section: Introductionmentioning
confidence: 99%